A low power high linearity baseband for a direct conversation CMMB tuner - 马何平 袁芳 石寅 兰晓明 代伐 (Journal of semiconductors, 2009)
An analog baseband circuit made in a 0.35-μm SiGe BiCMOS process is presented for China Multi-media Mobile Broadcasting（CMMB） direct conversion receivers.A high linearity 8th-order Chebyshev low pass filter（LPF） with accurate calibration system is used.Measurement results show that the filter provides 0.5-dB pass-band ripple,4% bandwidth accuracy,and-35-dB attenuation at 6 MHz with a cutoff frequency of 4 MHz.The current steering type variable gain amplifier（VGA） achieves more than 40-dB gain range with excellent temperature compensation.This tuner baseband achieves an OIP3 of 25.5 dBm,dissipates 16.4 mA under a 2.8-V supply and occupies 1.1 mm^2 of die size.